2016 49th Hawaii International Conference on System Sciences (HICSS) 2016
DOI: 10.1109/hicss.2016.426
|View full text |Cite
|
Sign up to set email alerts
|

Ingestible Biosensors for Real-Time Medical Adherence Monitoring: MyTMed

Abstract: Medication nonadherence complicates the management and treatment of chronic disease. Nonadherence to medications is associated with significant mortality, accelerated disease progression, and increased health care costs. My/Treatment/Medication (MyTMed) is a novel adherence monitoring system that obtains direct measures of medication adherence/nonadherence. MyTMed consists of 1) a “digital pill” with a radiofrequency emitter that activates on contact with gastric pH; 2) a relay Hub that captures the radiofrequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 31 publications
0
29
0
1
Order By: Relevance
“…From another point of view, non-adherence refers to the failure of taking medication as prescribed, including in-consistency, missing doses, and failing to re-fill the medication. Nonetheless, studies showed that failure to meet the medication-intake regime can result in emergence of drug resistance, accelerated progression of disease, many irrevocable health complications [23,24], and increased mortalities [25].…”
Section: Medication Adherencementioning
confidence: 99%
See 1 more Smart Citation
“…From another point of view, non-adherence refers to the failure of taking medication as prescribed, including in-consistency, missing doses, and failing to re-fill the medication. Nonetheless, studies showed that failure to meet the medication-intake regime can result in emergence of drug resistance, accelerated progression of disease, many irrevocable health complications [23,24], and increased mortalities [25].…”
Section: Medication Adherencementioning
confidence: 99%
“…MyTMed is another system for medication adherence monitoring that is based on ingestible biosensors [24,126]. The central part of MyTMed is the digital capsule that can encapsulate oral medication.…”
Section: Ingestible Biosensorsmentioning
confidence: 99%
“…Also, ingestible biosensors have been used to detect pill ingestion by patients to track medication adherence [15,16]. Currently, the use of ingestible biosensors has proved to be the most accurate, however, many patients will not find it convenient to ingest a biosensor so that they can be tracked to determine if they have taken their medication or not [3,15,17]. Proximity-based systems are non-invasive systems that detect medication presence or absence within the proximity of a reader's antenna by using computer vision technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…1217 Iterative improvements in data transmission and signal strength have made digital pills feasible and acceptable to pateints. 13 Formative data on the use of digital pills have demonstrated the ability to detect ingestion of antidiabetic agents, antipsychotics, and antituberculosis medications.…”
Section: Introductionmentioning
confidence: 99%